Pengembangan Blended Learning Interaktif Pada Pembelajaran Jarak Jauh Mata Kuliah Sejarah Dan Sosiologi - Puspita Pebri Setiani; Rizki Agung Novariyanto (Universitas Mathla'ul Anwar Banten, 2021)
lended learning is needed to improve the learning process and learning outcomes in distance learning during the COVID-19 pandemic. The purpose of this study is to develop interactive blended learning in distance learning in history and sociology courses. The method in this study uses Research And Development with the Borg & Gall model modified with ADDIE. The research was piloted on students of IKIP Budi Utomo Malang. The result of this research is an interactive blended e-learning of history and sociology developed based on the designed storyboard. The validity of interactive blended e-learning shows a valid category. The results of individual trials showed good category. The results of the small group trial were in the good category. The results of the field trials showed the good category.